REPRESENTASI PENINDASAN TERHADAP TOKOH UTAMA DALAM NOVEL JANJI KARYA TERE LIYE: KAJIAN KELAS SOSIAL - Nurhikmah Nurhikmah; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This research is entitled Representation of Oppression of the Main Character in the Novel Janji by Tere Liye: A Social Class Study. The purpose of this study is to describe the form of oppression and resistance of the main character in the novel Janji by Tere Liye with the study of Social Class. The problems raised regarding oppression include physical oppression, psychological oppression, and trade monopoly. Resistance includes self-sacrifice, fighting against social stigma, and struggling against inner conflicts associated with social class studies. The method used in this research is a qualitative method using a research approach that emphasizes the description of words or sentences to describe the phenomenon under study. This type of research is included in Library Research. Library research is a research method that uses literature sources, namely novels. The results showed that in the novel Janji by Tere Liye reflects social reality in the form of representation of oppression carried out by the upper class to the lower class and the resistance carried out by the lower class as a form of protection from oppression.